2010
DOI: 10.1111/j.1365-2109.2010.02643.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary phospholipids and highly unsaturated fatty acids on the precocity, survival, growth and hepatic lipid composition of juvenile Chinese mitten crab, Eriocheir sinensis (H. Milne-Edwards)

Abstract: Precocious puberty is one of the major constraints to the further development of Chinese mitten crab (Eriocheir sinensis) farming industry. Although dietary phospholipids (PL) and highly unsaturated fatty acids (HUFA) supplementation have been shown to enhance the growth of larval E. sinensis in other studies, it is still unknown whether this also leads to a higher precocity rate for juvenile E. sinensis. This study was conducted to investigate the e¡ects of dietary PL and HUFA on precocity, survival, growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Survival is an important criterion for the evaluation of culture performance of aquatic animals (Wu et al., ). This study showed WC had a lower survival rate than HP, which could be due to the large variation in body weight and aggressive behaviour of juveniles from the WC population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival is an important criterion for the evaluation of culture performance of aquatic animals (Wu et al., ). This study showed WC had a lower survival rate than HP, which could be due to the large variation in body weight and aggressive behaviour of juveniles from the WC population.…”
Section: Discussionmentioning
confidence: 99%
“…The precocious crabs, weighing between 15 and 35 g, have a low market value. Because precocious crabs have completed the terminal moult and reached precocious puberty, they are usually not used for stocking the grow‐out ponds in the following years (Wu et al., ). This has serious impacts on the economic profit of the E. sinensis farming industry (Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except improving growth, proper dietary fatty acid composition can also prevent the occurrence of precocity in crustacean (Lu et al . ; Wu, Wang, Cheng, Zeng, Yang & Lu ). In M. nipponense, the optimal dietary lipid content has been reported as 6–12% (Yu & Shen ), but the effects of lipid sources on growth and precocity have not been studied yet.…”
Section: Formulation and Proximate Analysis Of The Experimental Dietsmentioning
confidence: 99%
“…Soybean oil containing high n-6 polyunsaturated fatty acids (PUFA) was regarded to promote growth in leader prawn and red claw crayfish (Deering et al 1997;Li, Guo, Gan, Wang, Zhang & Zhao 2011), but in Penaeus vannamei and Litopenaeus vannamei, fish oil containing high n-3 highly unsaturated fatty acids (HUFA), such as 20:5n-3(EPA) and 22:6n-3(DHA), had better effect in promoting growth (Lim, Ako, Brown & Hahn 1997;Gonz alez-F elix, Lawrence, Gatlin & Perez-Velazquez 2002). Except improving growth, proper dietary fatty acid composition can also prevent the occurrence of precocity in crustacean (Lu et al 2010;Wu, Wang, Cheng, Zeng, Yang & Lu 2011). In M. nipponense, the optimal dietary lipid content has been reported as 6-12% (Yu & Shen 1990), but the effects of lipid sources on growth and precocity have not been studied yet.…”
mentioning
confidence: 99%